GEDUNG OLAHRAGA PENYANDANG TUNANETRA PADA KAWASAN KOMPLEK PERTUNI BANJARBARU - Hilpani, Muhammad Saidika; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Sports are very necessary for everyone's sports needs, including the blind. Blind people have limitations in their activities which is a problem in this writing. A special building was created for blind people to exercise in the PERTUNI Banjarbaru complex area using methods that can facilitate independence, comfort and safety when exercising. A design with the concept of orientation and mobility was chosen because this concept can prioritize comfort, comfort and safety for blind people. With this concept, it is hoped to produce a plan that suits the needs of blind people in carrying out sports activities.